Cash Bail and Systemic Inequity: A Socio-Legal Critique of Pretrial Justice and Marginalisation in Mombasa County (National Security: A Journal of the National Defence University-Kenya, 2025)
The apparatus of cash bail is devised to balance the presumption of innocence with a guarantee of court appearance, which has gradually railed against the existence of socioeconomic and ethnic inequality. This research yields a socio-legal critique of pretrial justice in Mombasa County, Kenya, examining how systemic bail inequities weaken governance credibility and intensify social exclusion. Utilising a multimethod approach, we explored thematic analysis of policy documents, court rulings, and NGO reports; interviews with police officers; regression modelling associating pretrial detention rates (2018–2023) with crime data; GIS-based hotspot mapping; and comparative case studies of bail reform in Germany and Canada. Quantitative results demonstrate that pretrial detention rates have an inverse relationship with community trust (β = –0.45, p < 0.01) and are inseparable from minor offences (3.2 % increase per 10 % rise in detention, p < 0.05), including terrorism recruitment. Logistic decline divulges that detention beyond seventy-two hours significantly raises the probability of reoffending in organised crime (OR = 1.8, p < 0.001). Spatial data analysis reveals coastal counties as points of interest where prolonged detention occurs simultaneously with radical activity. Qualitative intuitions bring to light that ethnic and economic discrimination in police bail decisions wears away civic faith and intensifies grievances that fanatic networks exploit. Considering experiences in other countries, we assert that impartial bail practices, emphasising risk-based assessments, non-monetary release options, and strengthened legal aid, are prerequisites for reinforcing social cohesion and national security. The analysis shows that pretrial justice updates should become part of security planning so bail works as a universal defence mechanism.
Keywords: Cash Bail, Systemic Inequity, Pretrial Justice, Social Exclusion, Socio-Legal Critique, Governance Credibility, Risk-based Assessments